1985
DOI: 10.1161/01.cir.72.5.1037
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of exercise stroke volume during ventricular versus atrial synchronous pacing: role of contractility.

Abstract: Although atrial synchronous and rate-responsive ventricular pacing have been compared, the importance of maintaining synchronized atrial systole in addition to rate responsiveness has been incompletely defined. That is, the effects of these two pacing modes on cardiac volumes and contractility have not been studied. Accordingly, 16 patients with normal ventricular function were studied while in the upright position and at rest with gated radionuclide ventriculography during both atrial synchronous and ventricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

1987
1987
2001
2001

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(13 citation statements)
references
References 41 publications
0
10
0
3
Order By: Relevance
“…Many, although, not all patients are symptomatic with palpitations, dyspnoea and decreased exercise capacity as the most important complaints. Symptoms associated with atrial fibrillation may relate to a loss of normal atrioventricular synchronization and loss of effective atrial contractions reducing cardiac output by 15–25% [4, 5]. Moreover, irregular R‐R intervals cause decreased cardiac output, increased pulmonary wedge pressure and increased right atrial pressure [6–9].…”
Section: Introductionmentioning
confidence: 99%
“…Many, although, not all patients are symptomatic with palpitations, dyspnoea and decreased exercise capacity as the most important complaints. Symptoms associated with atrial fibrillation may relate to a loss of normal atrioventricular synchronization and loss of effective atrial contractions reducing cardiac output by 15–25% [4, 5]. Moreover, irregular R‐R intervals cause decreased cardiac output, increased pulmonary wedge pressure and increased right atrial pressure [6–9].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Fananapazir et al 34 reported that the approximate 40% increase in exercise capacity associated with heart rate responsiveness in their patients (compared with fixedrate ventricular pacing) was independent of whether rate responsiveness was provided in conjunction with AV synchrony. The latter observations have been confirmed by Ausubel et al 35 although these investigators noted that at comparable rates the increased cardiac output achieved with single-chamber rate-responsive ventricular pacing was associated with a need to invoke compensatory contractile reserve as evidenced by Exercise Duration (minutes) with pacemakers, provision of both AV synchrony and an appropriate response in heart rate is desirable when feasible. On the other hand, for patients in whom primary atrial arrhythmias (e.g., atrial fibrillation, inexcitable atria) preclude maintenance of AV synchrony or in whom abnormal sinoatrial function results in symptoms caused by inadequate chronotropic responsiveness, a cardiac pacing system that provides an activity-initiated heart rate response permits quantitative (oxygen consumption, exercise duration) and qualitative (perceived exertion) improvements in exercise tolerance.…”
Section: Discussionmentioning
confidence: 71%
“…Our study would suggest that the importance of atrial systole to overall cardiac output in impaired ventricles without high filling pressure would increase further on exercise. This has indeed been shown in patients with heart block who have been paced either by ventricular stimulation alone and thus have atrioventricular asynchrony or with atrioventricular synchronous pacing (Pehrsson & Astrom, 1983;Ausubel, Steingart, Shimshi, Klementowicz & Furman, 1985).…”
Section: Discussionmentioning
confidence: 73%